Analysis of Student Engagement and Motivation Through Mobile Assisted Language Learning - Aulia Hanifah Qomar; Nur Akmal Maulana (Linguapedia, 2025)
The integration of Mobile-Assisted Language Learning (MALL) into educational practices has gained attention as an effective approach for enhancing language learning outcomes. This study investigates the impact of MALL on student engagement and motivation among vocational high school students in Metro City, Lampung, Indonesia. Using a qualitative case study method, data were collected through semi-structured interviews and classroom observations involving three purposively selected participants. This suggests the value of MALL, which, in achieving fun and interactive elements, promotes engagement and betterment of grammar and vocabulary. However, identified limitations in the internet connection remained, with little effect on speaking fluency. According to the research, viewed through the lens of Self-Determination Theory (SDT) as an analytical framework, one of the main advantages of MALL is the way it meets students' psychological needs for autonomy, competence, and relatedness. The implications suggest the necessity of integrating speaking activities into MALL tools, improving digital infrastructure, and customizing MALL applications for vocational education. This research contributes to the growing body of knowledge on technology-enhanced language learning, emphasizing its potential in specialized educational contexts.